Determination of Stratiform Cloud Formation and its effects upon Glacial Ablation at Linne'breen, Svalbard for the Summer of 2005 - Szembek, Carlos (2009)
Carlos'researched the formation of clouds over the Linne' Glacier and their roll in the overall rates of glacier ablation.